“Estudio de factores incidentes sobre la gestión de inventarios, caso Electromecánica Quimbita de la ciudad de Latacunga” - Quimbita Quimbita, Maritza Marivel (2021)
The present investigative work is elaborated based on the absence of an adequate control of the inventories in the microenterprise "Electromecánica Quimbita", having as background the above and the lack of it, generates deficiencies in the financial information and therefore in the operations. , preventing certainty in the amount of merchandise and causing not to make timely and necessary decisions at the time of the acquisition or sale of the different products. Based on this need, it is of vital importance to have a control of the merchandise that allows the registration of the different commercial transactions. In order to have theoretical bases on the best way to achieve efficient inventory management, a bibliographic review is made on topics such as inventory management and systems, stock, ABC system and warehouse management (Chapter I). With the theoretical bases, and with the investigation carried out in Quimbita Electromechanics, embodied in research instruments, it was possible, in the first instance, to make a diagnosis that points out incidents of inventory management carried out so far (Chapter II) and then propose actions to improve internal control, supervise the system, control the procedures and records implemented (Chapter III).